PENYELESAIAN SENGKETA MEDIK ANTARA DOKTER DAN PASIEN DI RUMAH SAKIT UMUM PERMATA BUNDA MEDAN - Rabithah Nazran; Suhaidi Suhaidi; Mahmud Mulyadi; Mahmul Siregar (Universitas Sumatera Utara, 2018)
ABSTRACT The medical dispute resolution in health is a part that never be released in health care in Indonesia The problems discussed in this thesis research are: First: how to resolve the medical dispute between doctor and patient at Permata Bunda General Hospital Medan?, Second: how is the responsibilities between doctor and patient at Permata Bunda General Hospital Medan?, Third: barriers what happens in the implementation of medical dispute settlement between doctor and patient at Permata Bunda General Hospital Medan? The method used in this study is the normative juridical and empirical juridical reference to the legal principles in the form of conception, norms, rules of law and collecting, finding data and information through case studies on the resolution of medical disputes between doctors and patients at Permata Bunda General Hospita Medanl. The nature of this thesis research is descriptive analysis. Technique of collecting data in this thesis research that is collecting of primary data with field study and collecting secondary data is by librarystudy. The conclusion in this thesis research is the resolution of medical disputes between doctors and patients at the Permata Bunda General Hospital Medan in civil law provides an alternative way of providing dispute settlement outside the court. Alternative Dispute Resolution (ADR) or alternative dispute resolution consists of conciliation, negotiation, mediation and arbitration. An analysis of cases of dispute resolution between doctors and patients at the Permata Bunda General Hospital Medan is the case of S.H. Siregar and M. Tarigan with the doctors and the Permata Bunda Medan General Hospital Medan that have been completed with the mediationpath. Keywords: Medical Dispute, Doctor, Patient, Permata Bunda General Hospital Medan.